Kinetic and Equilibrium Analysis of Estradiol in Uterus: A Model of Binding-Site Distribution in Uterine Cells - Williams, David (1972)
Kinetic and equilibrium binding studies indicate that the process by which the complex of estradiol-binding protein is transferred to the cell nuclei is very rapid and is readily reversible in intact cells; that is, the cytosol and nuclear binding sites are in a rapidly reversible equilibrium. Binding of the hormone appears to shift this equilibrium such that a large percent of the filled binding sites become associated with the nuclear fraction. A model is presented to show that the quantity of filled nuclear binding sites present at any estradiol concentration can be determined strictly by the initial binding between the hormone and the cytosol binding sites.